2022
DOI: 10.3233/jad-215199
|View full text |Cite
|
Sign up to set email alerts
|

Music, Mind, Mood, and Mingling in Alzheimer’s Disease and Related Dementias: A Scoping Review

Abstract: Background: Music-based interventions may help to alleviate neuropsychiatric symptoms of dementia and promote prosocial interactions between individuals living with dementia and their caregivers. However, current literature does not combine these evidence bases toward explanation of how music-based interventions may alleviate symptoms and promote prosocial interactions. Objective: We conducted a scoping review to address the following question: what do the evidence bases suggest toward how music therapy or mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…These findings suggest that listening to music contributes to emotion regulation, especially when the music is perceived as joyful and pleasant or possesses predictable, consonant harmonies. Moreover, studies utilizing music as a therapeutic intervention have already demonstrated the benefits of music-related activities on individuals [ 26 , 27 , 28 ], especially for positive emotions [ 27 , 29 ] and pro-social attitudes [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that listening to music contributes to emotion regulation, especially when the music is perceived as joyful and pleasant or possesses predictable, consonant harmonies. Moreover, studies utilizing music as a therapeutic intervention have already demonstrated the benefits of music-related activities on individuals [ 26 , 27 , 28 ], especially for positive emotions [ 27 , 29 ] and pro-social attitudes [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research on the use and benefits of music therapy among persons with end-stage dementia remains limited with a majority of studies examining cognitive function, behavioural and psychological functioning, and quality of life [ 14 ]. Despite the significant impairments associated with the disease, music interventions are accessible for people across the dementia spectrum and help to enhance cognitive functioning, promote social interactions and prosocial behaviours [ 15 , 16 , 17 ]. Research in the 1990s found that individuals in late-stage dementia could engage successfully with music through dancing and rhythm [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%